Fast Retrograde Signaling in Response to High Light Involves Metabolite Export, MITOGEN-ACTIVATED PROTEIN KINASE6, and AP2/ERF Transcription Factors in Arabidopsis . Issue 3 (25th March 2014) - Vogel, Marc Oliver; Moore, Marten; König, Katharina; Pecher, Pascal; Alsharafa, Khalid; Lee, Justin; Dietz, Karl-Josef
Abstract : This work finds that rapid retrograde signaling from the photosynthesizing chloroplast to alter nuclear gene expression involves a metabolite-linked pathway that depends on triose phosphate/phosphate translocator. Abstract: Regulation of the expression of nuclear genes encoding chloroplast proteins allows for metabolic adjustment in response to changing environmental conditions. This regulation is linked to retrograde signals that transmit information on the metabolic state of the chloroplast to the nucleus. Transcripts of several APETALA2/ETHYLENE RESPONSE FACTOR transcription factors (AP2/ERF-TFs) were found to respond within 10 min after transfer of low-light-acclimated Arabidopsis thaliana plants to high light. Initiation of this transcriptional response was completed within 1 min after transfer to high light. The fast responses of four AP2/ERF genes, ERF6, RRTF1, ERF104, and ERF105, were entirely deregulated in triose phosphate/phosphate translocator ( tpt ) mutants. Similarly, activation of MITOGEN-ACTIVATED PROTEIN KINASE6 (MPK6) was upregulated after 1 min in the wild type but not in the tpt mutant. Based on this, together with altered transcript regulation in mpk6 and erf6 mutants, a retrograde signal transmission model is proposed starting with metabolite export through the triose phosphate/phosphate translocator with subsequent MPK6 activation leading to initiation of AP2/ERF-TF gene expression and other downstream gene targets. The results show that operational retrograde signaling in response to high light involves a metabolite-linked pathway in addition to previously described redox and hormonal pathways.